Respuesta :
Answer:
- 1
Step-by-step explanation:
we need to know that
( a + b ) × ( a - b ) = [tex]a^{2} -b^{2}[/tex]
proof :
( a + b ) × ( a - b )
[tex]=a * a - a * b + a * b - b * b\\ = a * a - b * b\\= a^{2} - b^{2}[/tex]
so the ans is :
[tex]=2^{2} -(\sqrt{5} )^{2} \\=4 - 5\\=-1[/tex]
The product is -1.
We will use the FOIL method to find the product.
[tex]\left(2+\sqrt{5}\right)\left(2-\sqrt{5}\right)\\=4-2\sqrt{5}+2\sqrt{5}-\left(\sqrt{5}\right)^{2}\\=4-2\sqrt{5}+2\sqrt{5}-5\\=4-5\\=-1[/tex]
The product is -1.
Learn more: https://brainly.com/question/8806877